PENGARUH GAME EDUKASI DIGITAL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA DI KELAS V SEKOLAH DASAR - Tarigan, Rupina Magdalena Br; Sembiring, Polintan Rehulina; Tarigan, Sri Vita Oktapiani br (Universitas Negeri Medan, 2025)
This research aims to determine the effect of Digital Educational Games on student learning outcomes in science subjects in class V of SD Negeri 105316 Beranti. The type of research used is Quasi Experimental or quasi experimental research. The population in this study were all class V students. With class VA students totaling 22 students being the experimental class, using Digital Educational Game media. Then the VB class with 23 students became the control class, without using digital educational game media. Based on the research carried out, the experimental class pre-test results were obtained with an average of 64.00 and after carrying out treatment using Digital Educational Game media, the experimental class was given post-test questions. The post test score obtained by the experimental class was an average of 74.09. Meanwhile, the pre-test results obtained by the control class were an average of 30.00 and after carrying out treatment without digital educational media, the control class was given post-test questions. The post test score obtained by the control class was an average of 51.81. Based on the results of the t test that has been carried out, tcount = 2.106 and ttable obtained from the interpolation of t table data is 2.021. So we get tcount > ttable (2.106 > 2.021) which means that H0 is rejected and H1 is accepted, so there is a significant influence using digital educational media on the learning outcomes of class V students at SD Negeri 105316 Beranti. Based on the results of data testing, it can be concluded that there is a significant influence using digital educational media on the learning outcomes of fifth grade students in science subjects at SD Negeri 105316 Beranti for the 2024/2025 academic year.